The use of mother tongue in English classrooms in a Malaysian secondary School: a study of students' and teachers' perspectives / Zati Bayani Mohd Arifin - Mohd Arifin, Zati Bayani (2011)
The debate over whether English language classrooms should include or exclude students' native language has been a controversial issue for a long time. This study attempts to explore the use of mother tongue in English classrooms among secondary school students and teachers. It investigates both the students' and teachers' perceptions of the use of mother tongue in English classroom. Besides, it also explores to what extent mother tongue has an effect in facilitating students' acquisition process and helping them learn English. There are one hundred and eighteen students and four English teachers involved in this study. The data were collected by using questionnaires to the students as well as questioa»aires and interview to the teachers.The results showed that both students' and teachers' have positive perceptions of the use of mother tongue in English classroom. The results also showed that the use of mother tongue in English lessons facilitates the students learning of English. The use of mother tongue has been a means of providing students with the opportunities to enhance their understanding. Therefore, the findings of this study may be a rationale for English teachers in schools to consider mother tongue as a strategy for teaching English, especially to low English proficient students.